2003
DOI: 10.1523/jneurosci.23-23-08310.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Similarities and Diversities of Signal Pathways Leading to Consolidation of Conditioning and Consolidation of Extinction of Fear Memory

Abstract: It is generally believed that consolidation of long-term memory requires activation of protein kinases, transcription of genes, and new protein synthesis. However, little is known about the signal cascades involved in the extinction of memory, which occurs when the conditioned stimulus is no longer followed by the unconditioned stimulus. Here, we show for the first time that an intra-amygdala injection of transcription inhibitor actinomycin D at the dose that blocked acquisition failed to affect extinction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
201
3
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(221 citation statements)
references
References 62 publications
15
201
3
2
Order By: Relevance
“…The involvement of glutamate, and particularly its actions at N-methyl-D-aspartate (NMDA) receptors, is one of the most thoroughly investigated areas of the fear extinction literature. NMDA receptor antagonists block extinction of freezing and fearpotentiated startle when administered before extinction training either systemically or directly into the BLA [164][165][166][167][168] and block extinction of step-down avoidance when administered before extinction training directly into the CA1 region of hippocampus. 68,169 The effect is dose-dependent and not due to state dependency.…”
Section: Neurotransmitter Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of glutamate, and particularly its actions at N-methyl-D-aspartate (NMDA) receptors, is one of the most thoroughly investigated areas of the fear extinction literature. NMDA receptor antagonists block extinction of freezing and fearpotentiated startle when administered before extinction training either systemically or directly into the BLA [164][165][166][167][168] and block extinction of step-down avoidance when administered before extinction training directly into the CA1 region of hippocampus. 68,169 The effect is dose-dependent and not due to state dependency.…”
Section: Neurotransmitter Systemsmentioning
confidence: 99%
“…165,167 This is puzzling because CNQX completely blocks the expression of fear-potentiated startle, 178 and one might expect that a treatment that blocks expression of conditioned fear would also block extinction. In the report by Lin et al, 167 it is possible that the low levels of fear-potentiated startle observed in test were due to an impairment of fear expression by CNQX because the test was conducted 20 min after extinction training, when the drug likely had not yet been metabolized. However, this sort of explanation does not easily account for the results of Falls et al, 165 whose test was conducted 24 h after the completion of extinction training in the absence of additional infusions.…”
Section: Neurotransmitter Systemsmentioning
confidence: 99%
“…Until now, evidence in support of a role for NMDARs in fear extinction have come from experiments using systemic (Baker and Azorlosa, 1996;Santini et al, 2001;Suzuki et al, 2004) or intra-amygdala (Falls et al, 1992;Lee and Kim, 1998;Lin et al, 2003) injections of NMDAR antagonists that do not discriminate among NMDA subunit compositions. In addition to the fact that these studies do not distinguish between subunits, other issues complicate the interpretation of the results.…”
Section: Systemic Blockade Of Nr2b In Fear Extinction Learningmentioning
confidence: 99%
“…Although fear extinction also involves the amygdala (Davis et al, 2003), its role is less clear than in fear conditioning (Maren and Quirk, 2004;Sotres-Bayon et al, 2004). Much of the evidence implicating the amygdala in fear extinction has involved studies showing that blockade of N-methyl-D-aspartate receptors (NMDARs) in the lateral and basal amygdala, using APV (D,L-2-amino-5-phosphonovaleric acid), prevents the decrease in responding that normally occurs during extinction learning, as assessed in a later test (Falls et al, 1992;Lin et al, 2003). For technical reasons related to the behavioral paradigm used in these studies (fear-potentiated startle), it was not possible to assess the effects of NMDAR blockade during extinction learning.…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that a similar mechanism also is involved in the facilitatory effect of DEX on extinction. It is well known that numerous signaling cascades and immediate early genes are involved in extinction which include MAPKs, PI-3 kinase (Lu et al, 2001;Lin et al, 2003;Mansuy, 2003;Yang and Lu, 2005), calcineurin, zif268, and c-fos (Quirk et al, 2000;Herry and Garcia, 2002;Vianna et al, 2001). Activation of the amygdaloid glucocorticoid receptors may impair glutamate uptake in the amygdala, which could prolong the activation of amygdaloid NMDA receptors and result in activation of MAPKs signal cascades.…”
Section: Amygdaloid Glutamate Nmda Receptors Participate In the Modulmentioning
confidence: 99%